2005
DOI: 10.1163/1568551054922638
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and numerical analysis of compression after impact (CAI) behavior of CF/PIXA stiffened panels for HSCT structure

Abstract: Compression after impact (CAI) behavior of stiffened panels using T-shaped stringers made of heat resistant thermoplastic composites, CF/PIXA, was obtained by tests at room temperature and 180 • C. Excellent impact resistance in terms of delamination area was verified for the present composite panels due to the special fusion bonding film. Room temperature CAI strengths of the stiffened panels were found to be better than CF/PEEK panels in a rough comparison, without regard to differences in stacking sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…The first and second buckling loads were very similar to each other. The numerical results explained satisfactory the experimental results obtained by Ishikawa et al [1], where the average buckling load was about 290 kN and the buckling modes observed in the plate with uniform skin thickness and slightly tapered skin were 5-wave pattern and 4-wave pattern, respectively. Considering the efficiency of the calculation we basically adopted two layer models for convenience when further subdivision was not necessary to model the damaged portion.…”
Section: Numerical Results and Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The first and second buckling loads were very similar to each other. The numerical results explained satisfactory the experimental results obtained by Ishikawa et al [1], where the average buckling load was about 290 kN and the buckling modes observed in the plate with uniform skin thickness and slightly tapered skin were 5-wave pattern and 4-wave pattern, respectively. Considering the efficiency of the calculation we basically adopted two layer models for convenience when further subdivision was not necessary to model the damaged portion.…”
Section: Numerical Results and Discussionsupporting
confidence: 87%
“…We considered a blade-stiffened panel [1] made of carbon fiber and a high toughness and high thermal resistant resin (PIXA) as shown in Fig Table 1, where the 0 • direction is horizontal (x-axis) and transverse to the load as shown in Fig. 1.…”
Section: Numerical Model Of the Damaged Stiffened Panel And Finite Elmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of stiffeners on stress distribution around a hole, as well as on buckling and failure characteristics of lightweight composite panels, is the subject of the survey by Leissa (1987). More recently this subject was addressed in Degenhardt et al (2007), Diamanti, Soutis, and Hodgkinson (2007), Falzon, Davies, andGreenhalgh (2001), Found, Howard, andParan (2002), Greenhalgh and Hiley (2003), Greenhalgh and Garcia (2004) and Ishikawa, Matsushima, Hayashi, and Scott (2005) and numerous other publications mentioned in this chapter.…”
Section: Bounds For the Critical Controlled Parameters For Materials mentioning
confidence: 99%